KINERJA BALAI PENYULUHAN PERTANIAN, PERIKANAN DAN KEHUTANAN DALAM MENJALANKAN TUGAS DAN FUNGSI DI KABUPATEN LIMA PULUH KOTA (STUDI KASUS DI BP3K HARAU DAN BP3K LAREH SAGO HALABAN) - Jhony Hendra; Eri Gas Ekaputera, Hery Bachrizal Tanjung (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
The performance given by BP3K in carrying out its duties and functions can illustrate its role in facilitating the implementation of agricultural counseling in the District area, especially in the Lima Puluh Kota Regency. This study aims to explain the performance and factors related to the performance of BP3K Haraud and BP3K Lareh Sago Halabandalam in carrying out the duties and functions of the Minister of Agriculture. 26 of 2012. The research was conducted in January 2016-April 2017 at BP3K Harau and BP3K Lareh Sago Halaban. The approach used is qualitative with the type of case study research. The informants of this study were 14 people who came from civil servants, THL extension staff at BP3K Harau and BP3K Lareh Sago Halaban, 28 people who were Farmer Group Managers, Community Leaders and were taken using the snow ball purposive technique. Data collected by observation, interview and documentation techniques. The data analysis technique used is qualitative data analysis with analysis tools of narrative and interpretation data analysis. The conclusions obtained from this research are: Performance of BP3K Harau and BP3K Lareh Sago Halaban in carrying out their duties and functions based on the mandate of Permentan Number 26 of 2012 is in a condition that is still low, seen only one of the tasks and functions that can be carried out properly is to facilitate the preparation of sub-district agricultural extension programs while the other cannot be carried out properly by the two BP3Ks. Several factors that led to the low performance include: a) Internal factors such as the limited competency of the Agricultural Extension HR in both BP3Ks and the lack of support for facilities, agricultural extension infrastructure owned by the two BP3Ks; b) External factors such as funding support for agricultural extension services by local governments and support from the main actors (farmers) in the implementation of agricultural extension in the BP3K working area. Keywords: performance, agricultural extension facilities, the cost of agricultural extension services Agricultural Extension HR